2003
DOI: 10.1142/s0217979203016777
|View full text |Cite
|
Sign up to set email alerts
|

INCLINED SUBSTRATE DEPOSITED CeO2 FILMS BY ELECTRON BEAM EVAPORATION ON RANDOMLY ORIENTED METALLIC SUBSTRATE

Abstract: A study on CeCh film growth on randomly oriented metallic substrate using Inclined Substrate Deposition (ISD) technique was performed in order to develop a biaxially aligned buffer layer for YBa2Cu3C>7_5 (YBCO) coated conductors. The influence of deposition parameters, as the substrate inclination angle a with respect to the CeC>2 vapor direction, deposition temperature and film thickness, on structural and morphological properties of the film was investigated. At substrate temperature between 200°C and 700°C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Researchers are now able to grow crystalline superconductors with high critical currents on fine-grained substrates [8] by employing biaxially-textured template layers formed by ion-beam-assisted deposition (IBAD). A second approach to forming biaxial template layers is to use inclined substrate deposition (ISD) [9]. The essence of our proposed approach is to apply the process technology and basic approach developed for growing biaxially-textured superconductors on polycrystalline metal tapes to the challenge of growing biaxially-textured silicon on glass.…”
Section: Foreign Templates For Biaxially-textured Film C-si On Glassmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers are now able to grow crystalline superconductors with high critical currents on fine-grained substrates [8] by employing biaxially-textured template layers formed by ion-beam-assisted deposition (IBAD). A second approach to forming biaxial template layers is to use inclined substrate deposition (ISD) [9]. The essence of our proposed approach is to apply the process technology and basic approach developed for growing biaxially-textured superconductors on polycrystalline metal tapes to the challenge of growing biaxially-textured silicon on glass.…”
Section: Foreign Templates For Biaxially-textured Film C-si On Glassmentioning
confidence: 99%
“…Under the right conditions, the interaction of the ion beam and the growing film results in biaxial texture. Another possible route to biaxially-textured film growth is inclined angle deposition, where the depositing atoms themselves are incident at non-normal incidence to the substrate [9].…”
Section: Foreign Template Layer Growthmentioning
confidence: 99%
“…Finally, it has also been reported that biaxially textured oxide films can be grown by means of sputtering on polycrystalline substrates, which are inclined with respect to the sputter gun (ISD). [23][24][25] These techniques are physical vapour deposition methods and their industrial scaling-up is limited owing to the necessity of complex apparatus and slow deposition rates.…”
Section: Introductionmentioning
confidence: 99%
“…CeO 2 thin films have been grown by several techniques involving both physical and chemical methods. However, in the past few decades the metalorganic chemical vapor deposition (MOCVD) technique has been proved to be a suitable choice for the growth of ceramic thin films for numerous applications in solid-state electronic devices. In particular, we have recently reported on the unique example of CeO 2 thin films grown on TiO 2 substrate .…”
Section: Introductionmentioning
confidence: 99%